Optimal control algorithm of fertigation system in greenhouse based on EC model - Wu, Yong; Li, Li; Li, Shuaishuai; Wang, Hongkang; Zhang, Man; Sun, Hong; Sygrimis, Nikolaos; Li, Minzan (International Journal of Agricultural and Biological Engineering, 2019)
Two new control algorithms based on MSP430 microcontroller unit (MCU) were developed to improve the performance of a fertigation system controlled by the electrical conductivity (EC) value of an irrigation nutrient solution in a greenhouse. The first algorithm is incremental proportional–integral–derivative (PID), and the second one is a two-stage combination algorithm (PID + fuzzy). With an improved multi-line mixing Venturi tube, several sets of experiments are conducted for a fertilizer absorption test under two conditions, namely, various suction lines and different EC target values settings. Under the first condition, with an EC target value of 2.0 mS/cm and opening of various suction pipes, the steady-state times are 186 s, 172 s, 134 s, and 122 s corresponding to the opening of one to four suction pipes, respectively, for PID + fuzzy control. The corresponding values are 220 s, 196 s, 158 s, and 148 s for incremental PID control. Under the second condition, four suction pipes are opened with different target EC values of 1.5 mS/cm, 2.0 mS/cm, and 2.5 mS/cm, and the shortest response time and the minimum overshoot are obtained for PID + fuzzy control when the target EC value is 1.5 mS/cm, which are 96 s and 0.18 mS/cm, respectively. While the corresponding values are 112 s and 0.4 mS/cm respectively for incremental PID control. The two control strategies can adjust the EC value to the target value for real-time control, but the combination control algorithm can be implemented more rapidly, accurately, and steadily with a small overshoot compared with incremental PID control. The combination algorithm (PID + fuzzy) control strategy also possesses better properties for automatic fertigation control in greenhouses than the incremental PID control strategy, the combination algorithm provides an optimal way of water and fertilizer management for crops in greenhouses which will contribute to water and fertilizer saving.Keywords: fertigation, control algorithm, incremental PID, fuzzy control, irrigation control, greenhouseDOI: 10.25165/j.ijabe.20191203.4680Citation: Wu Y, Li L, Li S S, Wang H K, Zhang M, Sun H, et al. Optimal control algorithm of fertigation system in greenhouse based on EC model. Int J Agric & Biol Eng, 2019; 12(3): 118–125.